Identification of Potential Paleoislands in the Mediterranean Sea During the Last Glacial Cycle - Pablo Fraile Jurado; Juan Carlos Mejías-García (European Journal of Geography, 2025)
The Last Glacial Period (LGP) significantly altered sea levels and landscapes across the globe, with the Mediterranean Sea being no exception. During this period, fluctuating sea levels exposed numerous landmasses, some of which may have served as critical habitats for plants, animals, and even human populations. This study aims to identify and analyze the potential paleo-islands that were emerged in the Mediterranean Sea during the LGP (115,000 – 6,500 BP). Using high-resolution digital elevation models (DEMs) and bathymetric data, we reconstruct the Mediterranean’s paleogeography, focusing on the periods of maximum sea-level regression. A novel methodological approach was applied to determine the duration and extent of these paleo-islands, while filtering out uncertainties related to their size and elevation. Results show the existence of hundreds of potential paleo-islands, including larger landmasses that significantly expanded during this period. This research highlights the critical role these islands played in biogeographical processes, such as species migration and dispersal, and possibly in the migration patterns of early humans. Future work will focus on refining the data with localized sea-level curves and incorporating sedimentary and erosion processes into the analysis, providing a more comprehensive understanding of the Mediterranean’s geomorphological evolution